Formulation of business development strategies using BMC, SWOT and QSPM Methods (Case study on KWT Nine Seru in Lantan Village) - Mulyawati, Sri; Danasari, Idiatul Fitri (AGRICOLA, 2025)
Most Indonesian society relies on micro, small, and medium enterprises (MSMEs), as they are able to create and absorb up to 97% of the workforce. Some small businesses have not been able to grow significantly but still try to survive in the face of business competition. The Nine Seru Women Farmers Group (KWT) is one of the microbusiness groups that has survived COVID-19 until now. The unstable condition of KWT, both internally and externally, is an obstacle that is being faced. KWT needs a strategy relevant to its business's current condition. This research aims to formulate a business development strategy for KWT Nine Seru in Lantan Village. The methods used are BMC analysis to provide an overview of KWT Nine Seru's business model using nine key elements, SWOT analysis to formulate alternative business development strategies, and QSPM analysis to determine priority strategies. From the BMC analysis results, several business model improvements are offered to KWT Nine Seru, namely on key partnership elements, value proposition, channel, and cost structure. From the results of the SWOT analysis, eight combination strategies of SO, ST, WO, and WT were obtained. All alternative strategies were further analyzed using QSPM so that a priority strategy was obtained, namely keeping product prices competitive with market prices. The results of this study are important because they contribute to the fulfillment of the Sustainable Development Goals (SDGs), especially the first and second SDGs, namely no poverty and zero hunger. Through the strategies produced in this research, the KWT Nine Seru microbusiness group can survive the competition and develop its business so that it can avoid poverty and hunger due to not having a source of income.